A Note on The Butterflies of Gunung Belumut, Kluang Forest Reserve, Malaysia - Awg Abdul Rahman, Aqilah; Mohamed, Maryati (Journal of Sustainable Natural Resources, 2020)
A butterfly survey was done in Gunung Belumut Amenity Forest located within Kluang Forest Reserve, Johor. Sampling was done through manual collection using aerial nets and baited traps. A total of 128 individuals comprising 64 species were collected. Despite the high plant species richness in Kluang Forest Reserve, the butterfly diversity observed within Gunung Belumut Amenity Forest was relatively low when compared to other forested areas in Johor. This may be attributed to the abundance of oil palm plantation surrounding the area.  However, it is likely that there are more species within Kluang Forest Reserve, especially in the higher elevations of Gunung Belumut. Further sampling may add some new records to this checklist.